Supplementing growing Holstein steers fed a corn-urea diet with a mixture of essential amino acids increases performance - R.H. Wessels; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 1996)
Six ruminally cannulated Holstein steers (550 lb) implanted with Revalor-S were infused abomasally with water or a mixture of six amino acids in a crossover experiment (two 14-day periods) to evaluate effects on nitrogen balance. The mixture was comprised of amino acids that potentially may be limiting in lightweight steers, namely (g/day): lysine (5.3), methionine (3.3), threonine (3.2), tryptophan (1 .0), histidine (2.1), and arginine (5.5). Steers were fed at levels just below ad libitum intake. The diet contained 86% rolled corn, 10% prairie hay, 3% mineral and vitamin premixes, and 1% urea (as-fed). Amino acid infusion increased nitrogen retention by 17.9% over the control, from 27.9 g N/day to 32.9 g N/day. This indicates that implanted steers fed a high concentrate diet are able to respond to amino acid supplementation, suggesting that at least one of the infused amino acids was limiting in the basal corn-urea diet.
Keywords: Cattlemen' s Day; 1996; Kansas Agricultural Experiment Station contribution; no. 96-334-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 756; Beef; Holstein steers; Corn; Urea; Amino acids